DEVELOPMENT OF SCIENCE COMMUNICATION SKILLS AND LEARNING ACHIEVEMENT OF PRATOMSUKSA 5 STUDENTS ON THE TOPIC OF FORCE AND ENERGY BY USING PROBLEM-BASED LEARNING INTEGRATED WITH CONCEPT MAPPING - Aukepin , Pumai; Wattanasarn, Hassakorn; Pansuppawat, Anun (Journal of Educational Review Faculty of Education in MCU, 2025)
This research aims to 1) To develop a problem-based learning management plan with a conceptual structure of Prathomsuksa 5 students on the topic of Force and Energy to achieve the criteria of 80/80. 2) To compare science communication skills of Prathomsuksa 5 students before and after learning with problem-based learning Integrated with concept mapping. 3) Comparison of the learning achievement of Prathomsuksa 5 students before and after learning with problem-based learning Integrated with concept mapping. 4) To study the satisfaction of the Prathomsuksa 5 students with problem-based learning management Integrated with concept mapping. The sample, obtained through cluster random sampling, consisted of 40 Prathomsuksa 5 students, studying in the second semester of the 2024 academic year at Banpangkhon (Chapasamakkhiwitthaya) School. By group sampling, the statistics used in the research were mean, standard deviation. and independent group T-test statistics. The results showed that 1) A problem-based learning Integrated with concept mapping of Prathomsuksa 5 students on Force and Energy. It is as efficient as 84.47/80.46, which meets the 80/80 Criterion. 2) The compare science communication skills for Prathomsuksa 5 students, school were significantly higher than before Level of .01. 3) The academic achievement of Prathomsuksa 5 students after school was significantly higher than before at the level of .01. 4) The students were satisfied with the problem-based learning combined with concept mapping at the highest level.